Automatic English grammar test paper generation - Govin, Zillion (2017)
The rapid advancement in web technologies, followed by the ease of accessibility has caused a rapid improvement in the worldwide web environment. One of the innovation in web-based technology is no other than e-learning system. E-learning system has become increasingly popular as it is highly accessible and encourages self- learning in one’s own phase. Due to its popularity, many researches have been conducted to further increase the efficiency of learning in a web-based environment. This project focuses on the enhancement of a web-based learning system, Grammar Express, which serves as a platform to enhance the learning process in the field of English Grammar. This project aims to enhance the existing Grammar Express platform to cater for additional question types, such as Synthesis and Transformation, Grammar Cloze, and Editing. Additionally, the objective of this project is to research and implement an automatic Test Sheet Generation function based on multiple assessment criteria, also recognized as Test Paper Generation (TPG) feature. Evolutionary computing approach is researched and adopted in the process of developing the TPG feature. Furthermore, the algorithms are evaluated using performance benchmark defined by the author, and the evaluation results are analysed. In summary, the process of implementing the TPG feature, from the research phase to the evaluation phase, serves as the main focus of this report. Additional features such as Searching and Adaptive Testing are also discussed.